2023
DOI: 10.3390/vaccines11020414
|View full text |Cite
|
Sign up to set email alerts
|

Understanding COVID-19 Vaccine Hesitancy among Healthcare Workers in South Africa

Abstract: Healthcare workers (HCWs) were the first population group offered coronavirus disease 2019 (COVID-19) vaccines in South Africa because they were considered to be at higher risk of infection and required protecting as they were a critical resource to the health system. In some contexts, vaccine uptake among HCWs has been slow, with several studies citing persistent concerns about vaccine safety and effectiveness. This study aimed to determine vaccine uptake among HCWs in South Africa whilst identifying what dri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(21 citation statements)
references
References 64 publications
1
19
1
Order By: Relevance
“…Subsequent studies reported HCWs’ acceptance towards the COVID-19 vaccines [ 43 , 57 , 65 , 68 , 74 , 75 , 78 , 86 , 87 , 89 , 90 , 93 , 95 ]. Among these ten studies, over half of the participants were vaccinated with at least one dose (see Figure 2 ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Subsequent studies reported HCWs’ acceptance towards the COVID-19 vaccines [ 43 , 57 , 65 , 68 , 74 , 75 , 78 , 86 , 87 , 89 , 90 , 93 , 95 ]. Among these ten studies, over half of the participants were vaccinated with at least one dose (see Figure 2 ).…”
Section: Resultsmentioning
confidence: 99%
“…Within the theme of COVID-19 vaccines, ten sub-themes were identified, all acting as barriers to vaccine uptake. The most prominent sub-theme was safety concerns, which was reported as the primary barrier [ 23 , 25 , 43 , 47 , 50 , 51 , 55 , 56 , 57 , 60 , 61 , 65 , 66 , 67 , 68 , 69 , 70 , 72 , 74 , 75 , 76 , 77 , 78 , 81 , 82 , 83 , 84 , 85 , 86 , 88 , 90 , 91 , 92 , 95 ]. However, only three studies mentioned confidence in the COVID-19 vaccines, facilitating uptake [ 47 , 52 , 88 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Subgroup analyses were then conducted by replicating the models of potential predictors of COVID-19 vaccination uptake among two groups with perceptions or beliefs that have been shown to act as barriers to COVID-19 vaccine intentions: (1) those not trusting the safety of the vaccine5 11 12 31–33 and (2) those not believing the vaccine to be effective 14 34. The subgroup analyses aimed to identify factors that could potentially be leveraged to encourage vaccine uptake among individuals with common concerns about the vaccine.…”
Section: Methodsmentioning
confidence: 99%
“…The unprecedented pace of COVID-19 vaccine development contributed to widespread concerns over vaccine efficacy and safety 8–10. A growing body of evidence points to greater reluctance to get vaccinated among those concerned about the safety of COVID-19 vaccines5 11–13 and among those who do not believe they are effective 14 15…”
Section: Introductionmentioning
confidence: 99%